3
$\begingroup$

I am having trouble constructing the delta-epsilon proof for this limit. I am currently trying to find the delta in terms of epsilon:

$$\lim_{x \to 1} \frac{x^3-1}{\sqrt{x}-1}$$

So far I have gotten to

$$6-\epsilon < (x-1)*\frac{x^2+x+1}{\sqrt{x}-1} < 6+\epsilon$$

I am having trouble bounding the fraction $\frac{x^2+x+1}{\sqrt{x}-1}$ so that I can isolate $x-1$ and find the delta. It has a vertical asymptote at x=1, which makes it difficult to find an upper/lower bound.

Am I on the right track to this problem? If not, how would I go about finding the delta?

$\endgroup$
  • 2
    $\begingroup$ I would multiply and divide by $\sqrt{x}+1$ $\endgroup$ – Ninad Munshi Sep 15 at 20:22
  • 2
    $\begingroup$ Note that you can expand $(x-1)$ as $(\sqrt x + 1)(\sqrt x - 1).$ $\endgroup$ – md2perpe Sep 15 at 21:13
0
$\begingroup$

We have that for $x\neq 1$

$$\frac{x^3-1}{\sqrt{x}-1}=\frac{(x-1)(x^2+x+1)}{\sqrt{x}-1}=$$

$$=\frac{(\sqrt{x}-1)(\sqrt{x}+1)(x^2+x+1)}{\sqrt{x}-1}=(\sqrt{x}+1)(x^2+x+1)$$

and since for $|x-1|<1 \iff 0<x<2$, using triangle inequality and that $\forall a,b \:a\ge b\ge 0 \implies |x^a-1|\le |x^b-1|$, we obtain

$$\left|\frac{x^3-1}{\sqrt{x}-1}-6\right|=\left|(\sqrt{x}+1)(x^2+x+1)-6\right|\le\left|x^2\sqrt{x}+x^2+x\sqrt x+x+\sqrt{x}-5\right|\le$$

$$\leq |x^2\sqrt{x} -1|+\ldots +|\sqrt{x}-1| \leq 5|x^3 - 1| \le 5|x-1||x^2+x+1|\le 35|x-1|<\varepsilon$$

and it suffices to assume $\delta =\min\left(1,\frac{\varepsilon}{35}\right)$.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ How do I derive the statement $|x^2\sqrt{x} + x^2 + x\sqrt{x} + x + \sqrt{x} - 5| \leq |5x^3 - 5|$ ? I follow along until there. Thanks for your help! $\endgroup$ – avbdasf Sep 16 at 7:44
  • 1
    $\begingroup$ We have that for any $a>b>0 \implies |x^a-1|\le |x^b-1|$ then $$|x^2\sqrt{x} + x^2 + x\sqrt{x} + x + \sqrt{x} - 5| \leq |x^2\sqrt{x} -1|+\ldots +|\sqrt{x}-1| \leq 5|x^3 - 1|$$ I add this step also. $\endgroup$ – user Sep 16 at 7:51
0
$\begingroup$

Since $x\to 1$ set $x=(1+u)^2$ where $u\to 0$

Then $f(x)=\dfrac{(1+u)^6-1}{|1+u|-1}$, since $u$ is small $|1+u|=1+u$ and this simplifies to

$$f(x)= 6+15u+20u^2+15u^3+6u^4+u^5$$

But $u$ being small means we can take $|u|<1$ which implies $|u|^n<|u|$ for any $n$.

Thus $$|f(x)-6|\le (15+20+15+6+1)|u|=57|u|$$

For $|u|<1$ we have $|u+2|>1$ so $|u|<|u(u+2)|=|u^2+2u|=|(1+u)^2-1|=|x-1|$

Just take $$\delta=\min(1,\frac {\varepsilon}{57})\quad\text{we get}\quad|u|<|x-1|<\delta\implies |f(x)-6|\le 57|u|<\varepsilon$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.